The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1002/pi.1215
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of polypropylene/silver nanocomposite fibers

Abstract: Bicomponent sheath‐core fibers were prepared by a general melt‐spinning method with polypropylene chips and silver nanoparticles. The melt‐spun fibers were characterized by DSC, WAXS and SEM. The antibacterial effect was evaluated by an AATCC 100 test, a quantitative method. The results of the DSC thermogram and the intensity pattern of X‐ray diffraction indicated that the crystallinity of polypropylene including silver nanoparticles was slightly decreased compared with that of pure polypropylene fibers. SEM m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
69
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(78 citation statements)
references
References 6 publications
0
69
0
1
Order By: Relevance
“…As silver is non-toxic and posses antimicrobial properties, it has encouraged workers to use silver nanoparticles in different textile fabrics. In this direction, silver nanocomposite fibres were prepared containing silver nanoparticles incorporated inside the fabric [11]. Thus, various silver-based dressings have been introduced and have become the latest and greatest ''innovation'' in wound care products.…”
Section: Introductionmentioning
confidence: 99%
“…As silver is non-toxic and posses antimicrobial properties, it has encouraged workers to use silver nanoparticles in different textile fabrics. In this direction, silver nanocomposite fibres were prepared containing silver nanoparticles incorporated inside the fabric [11]. Thus, various silver-based dressings have been introduced and have become the latest and greatest ''innovation'' in wound care products.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been demonstrated that the antimicrobial activity of Ag NPs is higher than that of Ag ion [73]. The use of Ag NPs will lead to anti-bacterial effects maximized due to the increased numbers of particles per unit area [67]. Necula et al [55] have successfully fabricated Ag-bearing TiO2 coatings with different contents of Ag NPs by MAO in the electrolyte including CA, calcium glycerophosphate (Ca-GP) with Ag NPs.…”
Section: Introduction Of Metal Nanoparticles Into Mao Electrolytementioning
confidence: 99%
“…NPs present a greater chemical activity than the bulk material for the advantage of their larger ratio of surface area to volume [67]. Ag NPs are the most popular inorganic antimicrobial NPs [68] and can be incorporated into implant by directly dispersion of solid Ag NPs in the electrolyte during MAO.…”
Section: Introduction Of Metal Nanoparticles Into Mao Electrolytementioning
confidence: 99%
“…Polymeric or fibrous nanocomposites of polymers and silver nanoparticle have been reported to have special properties. [17][18] Nanocomposite fibers have attracted attention in recent years because improved mechanical, thermal, solvent resistance ad fire retardant properties compare to the pure or conventional composite fibers. Therefore, much work has focused on developing nanocomposite fibers using various polymers.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a coating of nano-particles on fabrics will not affect their breathability or hand feel. 7 For imparting anti-bacterial properties, nanosized silver, [8][9][10][11][12] titanium dioxide [13][14][15] and zinc oxides are used. Metallic ions and metallic compounds display a certain degree of sterilizing effect.…”
Section: Introductionmentioning
confidence: 99%